Delta‐9 desaturase reduction in gastrointestinal cells induced to senescence by doxorubicin - Valentina De Nunzio; Emanuela Aloisio Caruso; Matteo Centonze; Giuliano Pinto; Miriam Cofano; Ilenia Saponara; Maria Notarnicola (FEBS Open Bio)
The condition of cellular senescence has specific features, including an altered lipid metabolism. Delta‐9 desaturase (Δ9) catalyzes the conversion of saturated fatty acids, such as palmitic acid and stearic acid, into their monounsaturated forms, palmitoleic and oleic acid, respectively. Δ9 activity is important for most lipid functions, such as membrane fluidity, lipoprotein metabolism and energy storage. The present study aimed to investigate differences in the expression of Δ9 in senescence‐induced pancreatic (MIA‐PaCa‐2 and PANC‐1) and hepatic (Hepa‐RG and HLF) cancer cell lines. Cellular senescence was induced by growing cells in the presence of the chemotherapic drug doxorubicin. Senescence status was determined by the senescence‐associated beta‐galactosidase activity assay kit combined with the p21 and senescence associated secretory phenotype protein assay. Δ9 was downregulated in all senescence‐induced cell lines compared to control cells, in both the lipidomic analysis and when measuring protein levels via western blotting. Hence, our findings demonstrate that the study of membrane lipid composition and the expression levels of Δ9 could potentially form the basis for future applications investigating the state of cellular senescence.